Comprehensive mutational profiling of core binding factor acute myeloid leukemia - Duployez, Nicolas; Marceau-Renaut, Alice; Boissel, Nicolas; Petit, Arnaud; Bucci, Maxime; Geffroy, Sandrine; Lapillonne, Hélène; Renneville, Aline; Ragu, Christine; Figeac, Martin; Celli-Lebras, Karine; Lacombe, Catherine; et al. (Blood, 2016)
Acute myeloid leukemia (AML) with t(8;21) or inv(16) have been recognized as unique entities within AML and are usually reported together as core binding factor AML (CBF-AML). However, there is considerable clinical and biological heterogeneity within this group of diseases, and relapse incidence reaches up to 40%. Moreover, translocations involving CBFs are not sufficient to induce AML on its own and the full spectrum of mutations coexisting with CBF translocations has not been elucidated. To address these issues, we performed extensive mutational analysis by high-throughput sequencing in 215 patients with CBF-AML enrolled in the Phase 3 Trial of Systematic Versus Response-adapted Timed-Sequential Induction in Patients With Core Binding Factor Acute Myeloid Leukemia and Treating Patients with Childhood Acute Myeloid Leukemia with Interleukin-2 trials (age, 1-60 years). Mutations in genes activating tyrosine kinase signaling (including KIT, N/KRAS, and FLT3) were frequent in both subtypes of CBF-AML. In contrast, mutations in genes that regulate chromatin conformation or encode members of the cohesin complex were observed with high frequencies in t(8;21) AML (42% and 18%, respectively), whereas they were nearly absent in inv(16) AML. High KIT mutant allele ratios defined a group of t(8;21) AML patients with poor prognosis, whereas high N/KRAS mutant allele ratios were associated with the lack of KIT or FLT3 mutations and a favorable outcome. In addition, mutations in epigenetic modifying or cohesin genes were associated with a poor prognosis in patients with tyrosine kinase pathway mutations, suggesting synergic cooperation between these events. These data suggest that diverse cooperating mutations may influence CBF-AML pathophysiology as well as clinical behavior and point to potential unique pathogenesis of t(8;21) vs inv(16) AML. •Recurrent mutations in chromatin modifiers and cohesin were observed in t(8;21) AML, but not inv(16) AML.•t(8;21) AML patients with mutations in kinase signaling plus chromatin modifiers or cohesin members had the highest risk of relapse.